Consumer Protection Law Against Illegal Cosmetics With Hazardous Ingredients (Case Study BPOM Pekanbaru City) - Darnia, Meriza Elpha; Raditya, Masayu Adara; Genta, Muhammad; Deva, Deva; Ocsa, Asel Rahma; Juneid, Adiella Hadran Syah; Fajar, Jumatul (CV. Rayyan Dwi Bharata, 2023)
The purpose of this study is to find out and analyze consumer protection laws against cosmetics made from hazardous ingredients in Pekanbaru City based on BPOM regulations in Pekanbaru City. In addition, the purpose of this study is to find out the Regulations and Laws issued by the Ministry or Institution in law and BPOM in an effort to protect consumers. This research was conducted with Document Study research method and analyzed qualitatively with Thematic data analysis. In the preparation of this study, BPOM data studies and Ministry of Health Law and Literature Studies related to Consumer Protection Law were used with secondary data. The research material is then analyzed by explaining the values contained in laws and regulations with facts and data obtained. The results showed that the application of Consumer Protection of skin care products or cosmetics made from dangerous ingredients in Pekanbaru City